From 'cleanliness is next to Godliness' to 'without perfect health, there is nothing': discourses of healthy lifestyle in the construction of young adult identities in urban South Africa - De Jong, Michelle (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
This research explores popular constructions of "healthiness" as individual lifestyle choices in the context of contemporary South African consumer culture, and how these constructions relate to formations of subjectivity. This is a qualitative study conducted within a social constructionist, theoretical framework. Data was collected using in-depth, semi structured interviews and are analysed using a Foucauldian inspired version of discourse analysis. A critical stance is taken towards the assumption in these discourses that their version of healthiness is always and unquestionably positive. Special attention is paid to the lifestyle and marketing media discourses appropriated in understandings of personal health through self-management, and of the optimization of health in the pursuit of well-being. The ways in which different discourses of healthiness facilitate the construction of specific identities are considered in order to untangle some of the problems created by the moralism underpinning popular consumer health discourse. How constructions of healthiness and aspirant healthy lifestyles support, and are supported by, the ideologies and practices of neoliberal capitalism are also explored. From this perspective, healthiness as lifestyle consumption choices can be seen as an ideological apparatus that produces the subjects necessary to reproduce the social order (Althusser, 2001), functioning not only positively amongst the social classes with the leisure and economic resources to pursue these options, but also negatively as victim-blaming of those who are excluded. The argument here is not that health is bad or that people should not be bothered with activities aimed at promoting good health, but that in a context where the concept of health is idealised as always positive and beneficial, the potentially harmful consequences of some of the health discourses we make use of may be occluded. This idealisation of health or 'healthism' may also function to divert attention away from some of the challenges to health that are not the direct result of personal behaviours and are unlikely to be remedied through individually focussed interventions, for example, inequality and inadequate access to basic resources. Six discourses which were used to construct understandings of health are analysed. These include Happiness, Freedom, Control, Care, Balance and Goodness. The ways in which these discourses played a role in constructing the kinds of subject positions which were made available to participants, and the possible implications this has, are explored in depth.
Keywords: Health; Cleanliness; Social structure -- Health aspects; Health behavior; Social medicine